2022
DOI: 10.1186/s12871-022-01655-z
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia inhibited corticospinal excitability and attenuated the modulation of repetitive transcranial magnetic stimulation

Abstract: Background Lots of studies have measured motor evoked potential (MEP) induced by transcranial magnetic stimulation (TMS) in anesthetized animals. However, in awake animals, the measurement of TMS-induced MEP is scarce as lack of sufficient restraint. So far, the explicit study of anesthesia effects on corticospinal excitability and repetitive TMS (rTMS) induced modulation is still lacking. This study aimed to: (1) measure TMS-induced MEP in both awake restrained and anesthetized rats, (2) inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Previous studies also demonstrated that neuronal excitability and sensory responses in the somatosensory cortex did not present obvious differences between sedation with sufentanil and wakefulness (Bruno & Sakmann, 2006; Simons et al., 1992), probably due to the relatively sparse levels of μ‐opioid receptors in this cortical region (Sahin et al., 1992). Sufentanil sedation thus avoids significant anaesthesia‐related modulation of cortical responses to magnetic stimulation, as observed in both animal and human studies (Bradley et al., 2022; Gersner et al., 2011; Silvanto & Pascual‐Leone, 2008; Wang et al., 2022). Heart rate and ECoG activity were continuously monitored to assess the depth of sedation, and we ensured the stability of physiological parameters, i.e.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies also demonstrated that neuronal excitability and sensory responses in the somatosensory cortex did not present obvious differences between sedation with sufentanil and wakefulness (Bruno & Sakmann, 2006; Simons et al., 1992), probably due to the relatively sparse levels of μ‐opioid receptors in this cortical region (Sahin et al., 1992). Sufentanil sedation thus avoids significant anaesthesia‐related modulation of cortical responses to magnetic stimulation, as observed in both animal and human studies (Bradley et al., 2022; Gersner et al., 2011; Silvanto & Pascual‐Leone, 2008; Wang et al., 2022). Heart rate and ECoG activity were continuously monitored to assess the depth of sedation, and we ensured the stability of physiological parameters, i.e.…”
Section: Methodsmentioning
confidence: 94%
“…Brain state varies with the level of vigilance, voluntary attention, concurrent behaviour and anaesthesia. Unlike in human rTMS studies, in which changes to neuron excitability are only measured indirectly, assessment of single neuron intrinsic excitability over time in animals requires long‐lasting stable intracellular recordings and the use of anaesthesia, which depresses responses to rTMS (Chong et al., 2014; Sykes et al., 2016; Wang et al., 2022). To obtain physiologically relevant data, our LI‐rTMS protocol was conducted in animals sedated with the synthetic opioid sufentanil, which not only retains fast and small‐amplitude cortical waves that resemble those encountered in wakefulness (Altwegg‐Boussac et al., 2014, 2017), but also does not significantly modify somatosensory cortical neuron excitability and sensory responses in comparison to those measured in awake animals (Bruno & Sakmann, 2006; Simons et al., 1992).…”
Section: Discussionmentioning
confidence: 99%